Alcohol-induced hypertension: an important healthcare target in Belgium. Issue 6 (2nd November 2015) - Collart, F.; de Timary, P.; Dom, G.; Dor, B. D.; Duprez, D.; Lengele´, J.-P.; Matthys, F.; Peuskens, H.; Rehm, J.; Stärkel, P.
Abstract : Excessive alcohol intake is one of the leading causes of premature death in Europe and particularly in Belgium. Belgian people are consuming more alcohol per year than the European average. It is well established that excessive alcohol consumption is a significant predictor of the development of hypertension (HTN). Two million adults in Belgium suffer from HTN and this number will increase to three million by 2025.Less than 50% of Belgian people treated for HTN are well-controlled. Alcohol reduction in patients with HTN can significantly lower systolic and diastolic blood pressure. After reviewing the epidemiology of HTN and alcohol disorders in Belgium, this paper will focus on the rationale for alcohol screening and brief intervention in primary care. It will also describe the barriers to alcohol screening, and what could be the benefits of alcohol screening for our healthcare system. The authors believe that early identification through alcohol screening and brief intervention in general practice can help to improve the management of patients with HTN, to reach the targets of the WHO Global Action Plan, i.e., a 25% relative reduction in the risk of premature mortality from cardiovascular diseases, cancer, diabetes or chronic respiratory diseases. They are also convinced that this would allow achieving major healthcare savings.